SPIRITUAL MODULE IN DEVELOPING THE CONCEPT OF HUMAN BEING AS A KHALIFA (VICEGERENT): A RELIGIOUS REQUIREMENT IN COMPLYING AND REALISING THE RESPONSIBILITIES OF PROTECTING THE RELIGION (MAQASID HIFZ AL-DEEN) - Mohd Khairul Anwar Ismail; Mohd Nazri Mat Zin; Wan Nazihah Wan Mohamed; Zanirah Mustafa@Busu; Noraini Junoh; Nik Muniyati Nik Din (Journal of Islamic, Social, Economics and Development, 2022)
Islam is known as a religion that organizes the way of life covering aspects of faith, worship, family, politics, social and economic. The whole of human life and needs is organized completely and systematically by the teachings of Islam. Therefore, Islamic law is considered as the best rule and choice and its suitability with human nature has formed a civilization based on religious dotrin. The position of human as the caliph of Allah on earth is a great trust. Man will be held accountable for how he performs the sacred duties of his caliphate. However, in recent times, Muslims have experienced major crises that include spiritual, moral, faith and moral crises to the loss of human functions as slaves and caliphate of Allah SWT. The objective of this writing is to deeply interpret the role of human beings as the caliph of God and to detail the importance of religion in our lives as well as to identify the factors that deviate from religion. This study uses a qualitative descriptive research study approach. Library research is done through books, magazines and journals. In addition by conducting observational studies from previous research studies. The results found how important it is to understand our role as caliphs to make protection for the ummah and maintain the sustainability of the universe so that the caliph and the ummah must be united and love each other to live life in accordance with Islamic law for survival. The duties of the caliph in the Qur’an are commonly called imaratul ardh (prospering the earth) and ibadatullah (worshiping Allah). Therefore, this writing is very useful to give an understanding of the true purpose of God creating and assigning human to do imarah on earth by managing and preserving it.